Treatment of infected wounds of the abdominal wall after mesh hernia repair (Perioperaciina Medicina, 2022)
Background. An infected wound of the abdominal wall after mesh hernia repair is related to mesh infection, because mesh is situated at the bottom of the wound and granulation tissue doesn’t cover it. Infected mesh wounds have traditionally been treated by surgically removing the mesh which causes prolonged hospitalizations and hernia recurrence. Objective of the study is to increase the efficiency of treatment of wounds infection after mesh heria repair.Маterials and methods. We analyzed the results of wound infection treatment in 72 patients. 37 patients (group I) were treated according to the developed algorithm (ultrasound cavitation, VAC-therapy and decamethoxine solution), 35 (group II) were treated according to the traditional one (ultrasound cavitation, VAC-therapy and chlorhexidine digluconate solution).Results. The number of microbial colonies (CFU) in the wound decreased to lg (2.33 ± 0.51) CFU/ml and lg (1.35 ± 0.49) CFU/ml in group I against lg (4.01 ± 0) CFU/ml and lg (2.93 ± 0.56) CFU/ml in group II. (p < 0.01) The results of morphological examination of the wound edges confirmed more efficient growth of connective tissue in patients of group I (mesh was completely covered with granulation tissue) which improved wound healing. While in group II, mesh explantation was performed in 5 (14.3 %) patients (granulation tissue hasn’t covered mesh completely). The duration of wound healing in patients of group I was 16 ± 1.05 days, compared with 21 ± 1.2 days in group II (p < 0.01). We achieved better results through the use of the developed algorithm in group I, in particular the combination of ultrasound cavitation, VAC therapy and decametoxine solution, which has not only antimicrobial action, but also promotes connective tissue repair in the wound.Conclusion. Developed algorithm for wounds infection treatment after alloplasty, which includes ultrasound cavitation, VAC-therapy and decamethoxine solution, improves treatment outcomes, reduced wound healing time to 16 ± 1.05 days in patients of the main group against 21 ± 1.2 in comparison group, and excludes the possibility of mesh explantation in the main group against 14.3 % in the comparison group.
Keywords: wound infection of abdominal wall; mesh heria repair; abdominal hernia alloplasty; ultrasound cavitation; VAC therapy; decamethoxine solution; chlorhexidine digluconate solution